A Study of Internal Control Elements in PT. Guardian Pharmatama Employee Payroll Procedures : Kajian Unsur Pengendalian Internal pada Prosedur Penggajian Karyawan PT. Guardian Pharmatama - Annisa Sekar Khatulis Tiwi; Dwi Anggarani; Hartini Prasetyaning Pawestri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
This case study aims to determine how internal control is implemented in employee payroll procedures at PT. Guardian Pharmatama. The methods used are documentation, observation, and interviews. The analysis method used is descriptive qualitative analysis by describing and explaining the results of the case study in accordance with the theoretical basis. The results of this case study provide the conclusion that the implementation of internal control in employee payroll procedures at PT. Guardian Pharmatama cannot be said to be optimal even though the implementation of internal control is generally in accordance with the theoretical basis. This is because there are still weaknesses found in the implementation of internal control. The employee payroll procedure does not use the attendance recording function at the company. The attendance recording function at the company is not separate from the operational function. The recommendation given is to implement electronic attendance recording so that employee attendance is recorded directly.